Dogsred. 02 - Noda, Satoru (Viz signature., 2025)
As the school year comes to a close, it's time for the powerhouse Oinokami High ice hockey team to win the championship once again, but have they lost their edge? Then, after one of the biggest natural disasters in Japanese history, the people of northern Japan are determined to carry on. When the new school year starts, Rou and his friends from Miyamori enter Oinokami High School. They decide to try out for the hockey team, but before they can join, they have to survive a grueling daylong trial under the eye of the eccentric Coach Nihei.